Scaling Up Access to Electricity : The Case of Bangladesh - Sadeque, Zubair; Rysankova, Dana; Elahi, Raihan; Soni, Ruchi (World Bank, Washington, DC, 2014)
This knowledge note is the second of three case studies that concerns scaling up access to electricity in Africa, Bangladesh, and Rwanda. Since its inception in 2003, Bangladesh's solar home system program has installed about three million electrification systems in rural households, two-thirds of them in the last three years. The program is the most dynamic off-grid electrification program in the world, benefitting more than 15 million people and contributing about 130 MW in renewable energy generation capacity. The case study for Bangladesh is interesting, because off-grid electrification is crucial to reaching universal access. Achieving universal access to modern energy services is one of the three complementary objectives of the Sustainable Energy for All (SE4ALL) initiative. Bangladesh's rural electrification program was initiated in 1977 with the creation of the Rural Electrification Board (REB). Yet, it was estimated that at the prevailing pace of grid electrification, Bangladesh was going to take 50 years to reach universal access. By 2002, it had become apparent that an off-grid approach was needed to complement efforts to extend the grid. When the World Bank's first RERED project was being designed in 2002, a two-pronged approach was adopted to promote the use of solar home systems in rural areas, thereby leveraging the country's renewable energy potential, while continuing to help the REB and rural cooperatives improve their operational and financial performance. The program s final design is a good example of how international experience and local know-how can come together to yield an innovative design that suits the country's circumstances. The project's design was flexible (with a range of subsidies and system sizes, for example), allowing for quick adaptation to evolving technology and market conditions, and to consumer feedback.